2011
DOI: 10.1086/658333
|View full text |Cite
|
Sign up to set email alerts
|

Multihospital Outbreak ofClostridium difficileRibotype 027 Infection: Epidemiology and Analysis of Control Measures

Abstract: Objective.To report a large outbreak ofClostridium difficileinfection (CDI; ribotype 027) between June 2007 and August 2008, describe infection control measures, and evaluate the impact of restricting the use of fluoroquinolones in controlling the outbreak.Design.Outbreak investigation in 3 acute care hospitals of the Northern Health and Social Care Trust in Northern Ireland.Interventions.Implementation of a series of CDI control measures that targeted high-risk antibiotic agents (ie, restriction of fluoroquin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 38 publications
2
39
0
1
Order By: Relevance
“…The results from the swine isolates are consistent with other studies that have observed that the majority of isolates from swine are PFGE type NAP7 (21). Studies in human health care facilities have identified PFGE type NAP1 (ribotype 027) to be the virulent strain responsible for most of the recent outbreaks in North America and Europe (1,20,27). While no human clinical studies have made explicit mention of NAP7, studies have identified ribotype 078, toxinotype V isolates among human cases, and this is the strain most commonly associated with PFGE type NAP7 (17).…”
Section: Discussionsupporting
confidence: 88%
“…The results from the swine isolates are consistent with other studies that have observed that the majority of isolates from swine are PFGE type NAP7 (21). Studies in human health care facilities have identified PFGE type NAP1 (ribotype 027) to be the virulent strain responsible for most of the recent outbreaks in North America and Europe (1,20,27). While no human clinical studies have made explicit mention of NAP7, studies have identified ribotype 078, toxinotype V isolates among human cases, and this is the strain most commonly associated with PFGE type NAP7 (17).…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, fluoroquinolone use has been found to be a risk factor for infection by the NAP1/027 strain [2729] and the development of fluoroquinolone resistance by the NAP1/027 strain has been suggested to be the primary genetic factor facilitating its spread [29]. Fluoroquinolone restriction has also been reported to be an important component of efforts to control outbreaks of C. difficile from the NAP1/027 strain [30, 31], but further research is needed to determine the utility of the application of this strategy to non-outbreak settings.…”
Section: Discussionmentioning
confidence: 99%
“…Simply, this event may represent a coincidental occurrence of CDI cases with different strains; however, this cluster may also represent a potential outbreak or possible transmission events. It has been previously reported that different ribotypes may be present in a patient population during a C. difficile outbreak [25]. Additionally, transmission of C. difficile due to environmental contamination or by unidentified patients, staff, or visitors infected or colonized with C. difficile are also possible scenarios.…”
Section: Discussionmentioning
confidence: 99%